Communication in the workplace: request mitigations in Instant Messaging (IM) among native Malay speakers - Petani Mohd Noor,; Marlyna Maros,; Kesumawati Abu Bakar,; Normalis Amzah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In workplace communication, being polite and clear is essential. However, achieving both simultaneously can be challenging, particularly when dealing with face-threatening acts like making requests. Requests can infringe on someone’s freedom of action, potentially leading to face threats, necessitating facework strategies for restoration. One effective strategy is using external modifications or supportive moves to mitigate requests. Unfortunately, studies on requests among native Malay speakers have mainly focused on request cores, neglecting the investigation of request supportive moves. To address this gap, our qualitative study aims to explore request supportive moves used by native Malay speakers in instant messaging (IM) group communication. We analysed the data using strategy types of supportive moves by Fukushima (1996), supplemented with additional categories from Blum-Kulka and Olshtain (1984) and Konakahara (2011). Our findings revealed a preference for deferential supportive moves, with grounders being the most favoured type for mitigating requests. Our research highlights that communicatively competent native Malay speakers often use reasons as supportive moves to mitigate requests, regardless of the requests’ directness levels. Hence, it is advisable to mitigate requests with supportive moves generally or with grounders specifically when producing effective requests in the work environment. This approach allows native Malay speakers to present their requests clearly, politely and without imposing on others which in return helps to build quality relationships and keeps them productive.